The role of civil society in strengthening intercultural maternal health care in local health facilities: Puno, Peru - Jeannie Samuel (Taylor & Francis Group, 2016)
Background and objective: Peru's Ministry of Health has made efforts to increase the cultural inclusiveness of maternal health services. In 2005, the Ministry adopted an intercultural birthing policy (IBP) that authorizes and encourages the use of culturally acceptable birthing practices in government-run health facilities. However, studies suggest that indigenous women may receive inconsistent benefits from these kinds of policies. This article examines whether a grassroots accountability initiative based on citizen monitoring of local health facilities by indigenous women can help to promote the objectives of the IBP and improve intercultural maternal health care. Design: Findings are drawn from a larger qualitative research study completed in 2015 that included fieldwork done between 2010 and 2011. Semi-structured interviews were conducted with 23 women working as citizen monitors in local health facilities in Puno and 30 key informants, including frontline health workers, health officials, and civil society actors in Puno and Lima, and human rights lawyers from the Defensoría del Pueblo Office in Puno. Results: Monitors confirmed from their own personal experiences in the 1990s and early 2000s that respect for intercultural aspects of maternal health care, including traditional indigenous birthing practices, were not readily accepted in publicly funded health facilities. It was also common for indigenous women to face discrimination when seeking health service provided by the state. Although the government's adoption of the IBP in 2005 was a positive step, considerable efforts are still needed to ensure high-quality, culturally appropriate maternal health care is consistently available in local health facilities. Conclusions: Despite important progress in the past two decades, policies aimed at improving intercultural maternal health care are unevenly implemented in local health facilities. Civil society, in particular indigenous women themselves, can play an important role in holding the state accountable for quality care.